Risk Factors for Incident Falls and Fractures in Older Men With and Without Type 2 Diabetes Mellitus: The Concord Health and Ageing in Men Project. (27th February 2021) - Mesinovic, Jakub; Scott, David; Seibel, Markus J; Cumming, Robert G; Naganathan, Vasi; Blyth, Fiona M; Le Couteur, David G; Waite, Louise M; Handelsman, David J; Hirani, Vasant
Abstract: Background: Type 2 diabetes mellitus (T2DM) increases falls and fracture risk. Our objective was to compare incidence and risk factors for falls and fractures in community-dwelling older men with and without T2DM. Methods: A total of 1705 men (471 with T2DM; 1234 without T2DM) aged ≥70 years were assessed at baseline. Men were contacted every 4 months for 6.0 ± 2.2 years to ascertain incident falls and fractures, with the latter being confirmed by radiographic reports. Hip fractures were ascertained via data linkage (follow-up: 8.8 ± 3.6 years). Risk factors for falls and fractures included physical activity and function, body composition, medications, and vision measures. Results: Men with T2DM had similar fall (incident rate ratio [IRR]: 0.92 [95% confidence interval CI: 0.70, 1.12], n = 1246) and fracture rates (hazard ratio [HR]: 0.86 [95% CI: 0.56, 1.32], n = 1326) compared to men without T2DM after adjustment for significant risk factors. In men with T2DM, depression (IRR: 1.87 [95% CI: 1.05, 3.34], n = 333), sulphonylurea usage (IRR: 2.07 [95% CI: 1.30, 3.27]) and a greater number of prescription medications (IRR: 1.13 [95% CI: 1.03, 1.24]) were independently associated with increased fall rates, and higher total hip bone mineral density was independently associated with lower fracture rates (HR: 0.63 [95% CI: 0.47, 0.86], n = 351). Interaction terms demonstrated that better contrast sensitivity was independently associated with lower fracture rates (HR: 0.14 [95% CI: 0.02, 0.87]) in men with T2DM compared to men without T2DM. Conclusion: Fall and fracture rates were similar in men with and without T2DM after adjusting for significant risk factors. Vision assessments including contrast sensitivity measures may improve fracture prediction in older men with T2DM.